The Role of YouTube in Enhancing Learning Outcomes and Creativity among Elementary School Students - Desiyanti, Lina; Nuril Huda; Victor MTL Tobing (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
YouTube, a video-based platform, offers plenty of potential to help education by rendering it more interactive, engaging, and successful. However, the qualitative research conducted with a case study at Ba'engas 3 Elementary School at Labang district, Bangkalan city has yet to fully embrace YouTube as a teaching tool. Thus, this research uses a descriptive qualitative approach with the aim of discussing and analyzing in detail how the use of YouTube as a learning tool can improve students' learning outcomes and creativity. The research subjects consisted of the principal, teachers, and fifth-grade students of Ba’engas 3 Elementary School. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing and verification. The validity of the data was obtained through triangulation of sources and techniques. The research results show that the implementation of YouTube in learning for fifth-grade students at Ba’engas 3 Elementary School demonstrates high enthusiasm when learning using videos, making it easier to understand the material, and being able to develop creative ideas in the assigned project tasks. Students can gain a deeper and more contextual understanding of complex topics by using diverse and engaging YouTube audio-visual content. Thus, YouTube is not only a source of knowledge but also a tactical instrument to encourage creative and active learning as well as enhance students' understanding of the subject matter.